Energy cooperation between India and Central Asia - Asanbaev, M. B.; Baimenov, B. T. (Journal of Oriental Studies, 2016)
This article focuses on the role of Central Asia in the energy security policy of India. Energy is an integral part of the economy and foreign policy of any country.